2023
DOI: 10.26905/abdimas.v1i1.8703
|View full text |Cite
|
Sign up to set email alerts
|

Assistance for logo rebranding and packaging "Dodol Lima Pandawa" to improve product quality

Abstract: The use of online media in the process of selling products is intended to help the community more easily in terms of marketing in line with the post-Covid 19. The implementation of this community empowerment depends on the ability of the community or mothers who have small businesses in Tebing Gerinting Village, South Indralaya. One of the main pillars of the Indonesian economy is to develop small businesses in villages that are run directly by the local community without any third party. Villages are somethin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 10 publications
0
2
0
Order By: Relevance
“…MSMEs ought to be complementary to Indonesia's employment needs, particularly in the context of unemployment because the growth of such enterprises will significantly enable the development of the nation's economy. In Indonesia, policies to promote the development of MSMEs are crucial since they are great potential tools that can help decrease unemployment and poverty [25]. Analysis conducted on unemployment and the growth of Indonesia's economy has indicated that the growth of MSMEs is positive and significant to unemployment in the country [26].…”
Section: Msme and Unemploymentmentioning
confidence: 99%
See 1 more Smart Citation
“…MSMEs ought to be complementary to Indonesia's employment needs, particularly in the context of unemployment because the growth of such enterprises will significantly enable the development of the nation's economy. In Indonesia, policies to promote the development of MSMEs are crucial since they are great potential tools that can help decrease unemployment and poverty [25]. Analysis conducted on unemployment and the growth of Indonesia's economy has indicated that the growth of MSMEs is positive and significant to unemployment in the country [26].…”
Section: Msme and Unemploymentmentioning
confidence: 99%
“…Further, the increase in the expansion of MSMEs has been linked to the overall increase welfare of workers in the relevant enterprises and therefore underlines their influence on eradicating high unemployment rates [33]. Adequate initiatives to foster and enhance the development of the MSME sector have been underlined as critical not only in absorbing the available workforce but also in proactively working towards improving working conditions, which will translate to reductions in unemployment levels [25].…”
Section: Poverty and Unemploymentmentioning
confidence: 99%